Factors and Situations Affecting the Value of Patient Preference Studies: Semi-Structured Interviews in Europe and the US - Whichello, Chiara; van Overbeeke, Eline; Janssens, Rosanne; Schölin Bywall, Karin; Russo, Selena; Veldwijk, Jorien; Cleemput, Irina; Juhaeri, Juhaeri; Levitan, Bennett; Kübler, Jürgen; Smith, Meredith; Hermann, Richard; et al. (Frontiers in Pharmacology, 2019)
Objectives Patient preference information (PPI) is gaining recognition among the pharmaceutical industry, regulatory authorities, and Health Technology Assessment (HTA) bodies/payers for use in assessments and decision-making along the medical product lifecycle (MPLC). This study aimed to identify factors and situations that influence the value of patient preference studies (PPS) in decision-making along the MPLC according to different stakeholders. Methods Semi-structured interviews (n=143) were conducted with six different stakeholder groups (physicians, academics, industry representatives, regulators, HTA/payer representatives, and a combined group of patients, caregivers, and patient representatives) from seven European countries (the United Kingdom, Sweden, Italy, Romania, Germany, France, and the Netherlands) and the United States. Framework analysis was performed using NVivo 11 software. Results Fifteen factors affecting the value of PPS in the MPLC were identified. These are related to: study organisation (expertise, financial resources, study duration, ethics and good practices, patient centeredness), study design (examining patient and/or other preferences, ensuring representativeness, matching method to research question, matching method to MPLC stage, validity and reliability, cognitive burden, patient education, attribute development), and study conduct (patients’ ability/willingness to participate and preference heterogeneity). Three types of situations affecting the use of PPS results were identified (stakeholder acceptance, market situations, and clinical situations). Conclusion The factors and situation types affecting the value of PPS, as identified in this study, need to be considered when designing and conducting PPS in order to promote the integration of PPI into decision-making along the MPLC.